Organisational strategies for changing clinical practice: how trusts are meeting the challenges of clinical governance. Issue 2 (1st June 2001) - Wallace, L M; Freeman, T; Latham, L; Walshe, K; Spurgeon, P
Abstract : Objectives —To describe the use, perceived effectiveness, and predicted future use of organisational strategies for influencing clinicians' behaviour in the approach of NHS trusts to clinical governance, and to ascertain the perceived benefits of clinical governance and the barriers to change. Design and setting —Whole population postal survey conducted between March and June 1999. Subjects —Clinical governance leads of 86 NHS trusts across the South West and West Midlands regions. Method —A combination of open questions to assess the use of strategies to influence clinician behaviour and the barriers to clinical governance. Closed (yes/no) and Likert type ratings were used to assess the use, perceived effectiveness, and future use of 13 strategies and the predicted outcomes of clinical governance. Results —All trusts use one or more of 13 strategies categorised as educational, facilitative, performance management, and organisational change methods. Most popular were educational programmes (96%) and protocols and guidelines (97%). The least popular was performance management such as use of financial incentives (29%). Examples of successful existing practice to date showed a preference for initiatives that described the use of protocols and guidelines, and use of benchmarking data. Strategies most frequently rated as effective were facilitative methods such as the facilitation of best practice in clinical teams (79%), the use of pilot projects (73%), and protocols and guidelines (52%). The least often cited as effective were educational programmes (42%) and training clinicians in information management (20%); 8% found none of the 13 strategies to be effective. Predicted future use showed that all the trusts which completed this section intended to use at least one of the 13 strategies. The most popular strategies were educational and facilitative. Scatterplots show that there is a consistent relationship between use and planned future use. This was less apparent for the relationship between planned use and perceived effectiveness. Barriers to change included lack of resources, mainly of money and staff time, and the need to address cultural issues, plus infrastructure support. The anticipated outcomes of clinical governance show that most trusts expect to influence clinician behaviour by improving patient outcomes (78%), but only 53% expect it to result in better use of resources, improved patient satisfaction (36%), and reduced complaints (10%). Conclusions —Clinical governance leads of trusts report using a range of strategies for influencing clinician behaviour and plan to use a similar range in the future. The choice of methods seems to be related to past experience of local use, despite equivocal judgements of their perceived effectiveness in the trusts. Most expect to achieve a positive impact on patient outcomes as a result. It is concluded that trusts should establish methods of learning what strategies are effective from their own data and from external comparison.